The Biological potential and performance of Bayantsagaan sheep with more vertebra - Purev, Chimgee; Gendenjamts, Altangerel; Banzragch, Ganbaatar; Damdingombo, Zorigtbaatar (Mongolian Journal of Agricultural Sciences, 2022)
In this study, we aim to analyze and compare meat yield differences between Bayantsagaan sheep with vertebral count variations and sheep with normal vertebrae counts; meat yield measurement data was operationally defined via live weight, body size, and slaughter weight data points. Body weight and measurement data were collected and statistically analyzed from randomly selected sheep varying from seven months to six years of age (n = 300). For the meat yield determination research context, sheep with vertebral number variations (n=286) and sheep with a normal vertebral number (n=14) were brought from different 10 households of Bayantsagaan soum of the Tuv province to the slaughterhouse and were selected by age group. As a result, the coefficient variation of the extra vertebrae sheep’s live weight was 6.9-17.8% for males and 9.8-17.4% for females; this shows that the live weight of the extra vertebrae sheep was more variable and had more biological resources to increase weight and meat yield based on selective breeding programs. In terms of body size and meat production, there were no significant differences between the sexes, but there were significant differences between the sheep with extra vertebrae and the normal sheep (P < 0.05), illustrating the genetic basis of these traits. The body length (BL) of 0.7-2-year-old rams with extra vertebrae was on average 5 cm (P≤0.01) longer than the control normal sheep. Additionally, mature rams exhibited higher body lengths than the younger rams (p < 0.01). The heart girth (HG) of the sheep with extra vertebrae was an estimated 4.9 cm (P≤0.01) and 1.4 cm (P≤0.01) longer than the normal sheep. The slaughter weight of the rams with the extra vertebrae was an estimated 3.5 kg higher than the normal rams, and the yield was 1.4% higher. Based on the average herd rate, the carcass weight and the slaughter yields of the sheep with the extra vertebrae were estimated at 0.9-3.3 kg or 1.8-2.7% more than the normal sheep. By taking advantage of the extra vertebral features in the selection criteria of the breeding program, meat production can be increased throughout the herd. Хэц ясны хувьсамжтай баянцагаан хонины аж ахуй, биологийн чадавхи Хураангуй: Бид энэхүү судалгаагаар Баянцагаан хонины хэц ясны хувьсамжтай ба хувьсамжгүй хонины амьдын жин, биеийн хэмжээ, нядлагын жин, гарц ба цэвэр махны гарц зэрэг махан ашиг шимийн үзүүлэлтийг тодорхойлохыг зорьсон ба шаардлагатай зоотехникийн үндсэн хэмжээснүүдийг, 10 суурь (айл)-иас, n=300 хонийг тохиолдлын аргаар сонгон хийж, ашиг шимийн болон морфологийн үзүүлэлтүүдэд статистик боловсруулалт хийв. Махан ашиг шимийг тодорхойлох судалгаанд хувьсамжтай ба хувьсамжгүй n=14 хонийг насны ангиллаар сонгон хяналтын нядалгааг хийж, судалгааг материал арга зүйн хэсэгт дурдсаны дагуу зоотехникийн аргыг ашиглан явуулав. Судалгааны үр дүнд, Баянцагаан хонины амьдын жингийн хувьсамтгай чанарын илтгэлцүүр илүү нугаламтай эр хонинд 6.9-17.8%, эм хонинд 9.8-17.4% байгаа нь энэ хонины амьдын жин хувьсамтгай чанар өндөртэй бөгөөд хонийг өөр дотор нь сонгон үржүүлэх үндсэн дээр жин, махны гарцыг нэмэгдүүлэх биологийн нөөц байгааг харуулж байна. Биеийн хэмжээс болон махан ашиг шимийн хувьд хүйсийн хооронд мэдэгдэхүйц ялгаа ажиглагдаагүй боловч хувьсамжтай болон энгийн хонины хооронд ажиглагдсан (P <0.05) нь эдгээр шинж тэмдгүүдийн генетикийн үндэслэлийг илтгэнэ. Илүү нугаламтай 0.7-2 настай эр төлөгний биеийн ташуу урт хяналтын буюу энгийн хониноос дунджаар 5 см-ээр (P≤0.01), харин нас гүйцсэн эр хониных дунджаар 1.3 см-ээр (P≤0.01), цээжний бүслүүр дээрхи дарааллаар 4.9 см (P≤0.01), 1.4 см-ээр (P≤0.01) урт байлаа. Илүү нугаламтай эр хонины нядлагын жин 36.2 кг, гарц нь 51.7% байсан бол хяналтын буюу энгийн эр хонины нядлагын жин 32,7 кг, гарц нь 50.3% байсан ба нядлагын жин 3.5кг-аар, гарц нь 1.4 %-иар илүү байлаа. Сүргийн дунджаар, хувьсамжтай буюу нугалам нэмэгдсэн хонины гулуузны жин, нядлагын гарц жирийн хониныхоос 0.9 кг -3.3 кг буюу 1.8-2.7 хувь илүү байна. Энэхүү хонины хэц ясны хувьсамжаар шилэлт хийж үржүүлэгт ашиглан махан ашиг шимийг нэмэгдүүлэх ажлыг системтэйгээр хийснээр нийт сүргийн хэмжээнд мах үйлдвэрлэлийг жигд нэмэгдүүлэх боломжтой болох юм. Түлхүүр үг: хэц ясны хувьсамж, цээжний бүслүүр, биеийн ташуу урт, нядлагын жин, гарц